Quality, Access, and Competitiveness in Islamic Religious Education: A Critical-Historical Analysis of Policy Implementation at Al-Ikhlash Junior High School - Ma’ani, Arifatul; Faridi, Faridi; Tobroni, Tobroni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study investigates the evalution of Islamic Religious Education (IRE) policies in Indonesia and their impact on educational quality, access, and institutional competitiveness. A case study of Al-Ikhlash Junior High School in Lumajang was conducted using a critical-historical methodology, combining document analysis of national education policies (1989–2023), field observations, and in-depth interviews with 15 stakeholders. The findings indicate a significant policy shift from domestication to accommodation, marked by the integration of IRE into the national curriculum and the enhancement of the learning environment. Key outcomes include: (1) improved educational quality through the development of contextual curricula and teacher training programs, (2) increased access via inclusive admission policies and infrastructure investments, and (3) enhanced institutional competitiveness, evidenced by student achievements in national religious competitions. Despite these advancements, challenges such as technological disparities and uneven resource distribution remain. Theoretically, this research contributes to the field of policy implementation by highlighting how local actors adapt national mandates. Practically, it offers three strategies for optimizing IRE: (a) digital upskilling for educators, (b) public-private partnerships to strengthen infrastructure, and (c) curriculum moderation that balances religious values with 21st-century skills.